The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s001980200000
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Bone: Determinants of Skeletal Fragility and Bone Quality

Abstract: Bone fragility can be defined by biomechanical parameters, including ultimate force (a measure of strength), ultimate displacement (reciprocal of brittleness) and work to failure (energy absorption). Bone fragility is influenced by bone size, shape, architecture and tissue 'quality'. Many osteoporosis treatments build bone mass but also change tissue quality. Antiresorptive therapies, such as bisphosphonates, substantially reduce bone turnover, impairing microdamage repair and causing increased bone mineraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
290
1
24

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(332 citation statements)
references
References 25 publications
11
290
1
24
Order By: Relevance
“…Additionally, variability in both mineralization (48)(49)(50) and the local mineral content (51-53) due to disease or osteoporosis treatments are known to affect the mechanical properties and may play a role in aging. We believe that the age-related increase in microdamage originates at the fibrillar level; however, changes in the location (42) or nature (54,55) of microcracking with age may further reveal how this role of microcracking contributes to the toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, variability in both mineralization (48)(49)(50) and the local mineral content (51-53) due to disease or osteoporosis treatments are known to affect the mechanical properties and may play a role in aging. We believe that the age-related increase in microdamage originates at the fibrillar level; however, changes in the location (42) or nature (54,55) of microcracking with age may further reveal how this role of microcracking contributes to the toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite crystals constitute the mineral components of bone [2,3,7,21]. The mechanical properties of the vertebra (stiffness, strain, ultimate load, etc.,) are related to the extent of mineralization of the bone matrix [7,22]. Currey [5] demonstrated that observed torsional strength is proportional to and most depended on mineral content.…”
Section: Discussionmentioning
confidence: 99%
“…That is why the knowledge about changes in elastic properties and the effective thickness of the cortex are of equal diagnostic value for better assessment of different types of osteopenia and detecting osteoporosis development in long bones at earlier stages. Thinning of the cortex is one of the main indicators of decreasing total bone strength and capacity to withstand fracturing [12]. The elastic properties also can be altered by appearance of inner pores and accumulation of microcracks, as well as by degree of mineralization, i.e.…”
Section: Introductionmentioning
confidence: 99%